DIGITAL INTEGRATED MARKETING COMMUNICATIONS (DIMC) ACTIVITIES OF DIGITAL PRODUCTS FINANCIAL TECHNOLOGY (FINTECH) “ALAMI” - Baharudin Noveriyanto; Sa’diyah El Adawiyah (Profetik: Jurnal Komunikasi, 2021)
Abstract. The development of information and communication technology has now had a major impact on the industrial world in Indonesia. Changes in the industrial model towards digital have a major influence on marketing activities carried out by companies so that they can win the competition in the midst of increasingly sharp business competition. The ability to adapt and innovate quickly and precisely by involving various digital communication media and marketing technology will have a positive influence on the company. ALAMI is a digital-based sharia financial product brand (financial technology), where the name ALAMI is taken from the prefix of the verse in the Al-Quran, namely "Alif, Lam, Mim" which is then shortened to ALAMI. This study aims to determine the activities of digital integrated marketing communication (DIMC) in digital financial technology (fintek) products ALAMI, which consist of digital advertising, digital personal selling, digital sales promotion, digital public relations and digital direct marketing. This study uses a qualitative approach that focuses on the concept of integrated marketing communication (IMC) Kotler (2008) which consists of advertising, personal selling, sales promotion, public relations and direct marketing conducted digitally for financial technology products ALAMI. The main conclusion of this research is that the application of digital integrated marketing communication in digital financial products ALAMI can be done well, and is efficient in terms of costs. The concept of digital integrated marketing communication (DIMC) is a form of transformation of the concept of integrated marketing communication (IMC) whose implementation activities are adjusted to technological developments and the characteristics of the current digital industry. Abstrak. Perkembangan teknologi informasi dan komunikasi kini telah berdampak besar terhadap dunia industri di Indonesia. Perubahan model industri kearah digital memberikan pengaruh besar pada kegiatan pemasaran yang dilakukan oleh perusahaan agar dapat memenangkan kompetisi ditengah-tengah persaingan bisnis yang semakin tajam. Kemampuan melakukan adaptasi dan inovasi dengan cepat dan tepat dengan melibatkan berbagai media komunikasi digital dan teknologi pemasaran akan memberikan pengaruh positif kepada perusahaan. ALAMI adalah sebuah merek produk keuangan syariah berbasis digital (financial technology), dimana nama ALAMI ini diambil dari awalan ayat dalam Al-Quran, yaitu “Alif, Lam, Mim” yang selanjudnya disingkat menjadi ALAMI. Penelitian ini bertujuan untuk mengetahui aktifitas digital integrated marketing communication (DIMC) pada produk digital financial technology (fintek) ALAMI yang terdiri dari digital advertising, digital personal selling, digital sales promotion, digital public relation  dan digital direct marketing. Penelitian ini menggunakan pendekatan kualitatif yang memfokuskan pada konsep aktifitas Integrated Marketing Communication (IMC)  Kotler (2008) yang terdiri dari advertising, personal selling, sales promotion, public relation  dan direct marketing berbasis digital untuk produk financial technology ALAMI. Kesimpulan utama dari penelitian ini adalah bahwa penerapan digital integrated marketing communication pada produk keuangan digital ALAMI dapat dilakukan dengan baik, dan efisien dalam segi biaya. Konsep digital integrated marketing communication (DIMC) adalah salah satu wujud dari trasformasi konsep integrated marketing communication (IMC) yang implementasi kegiatannya disesuikan dengan perkembangan tekonology dan karakteristik industry digital saat ini.